Fiscal Consolidation: Part 4. Case Studies of Large Fiscal Consolidation Episodes - Blöchliger, Hansjörg (OECD Publishing, 2012)
This paper provides an analysis of large and sustained fiscal consolidation episodes in OECD countries implemented between 1980 and 2000. It reviews how fiscal policy variables evolved during these episodes, how consolidation was influenced by the wider economic environment, and how the political economy side helped trigger and sustain consolidation efforts. Results suggest that successful consolidation - as measured by deficit reduction and debt stabilisation or decline - was driven by spending cuts and to a lesser extent by revenue increases. Most episodes started on a basis of improving competitiveness following currency depreciation and, in turn, favourable growth prospects, closing output gaps and - with some lag - falling unemployment. Interest rates started to decline two years after consolidation had started, suggesting that it took some time to earn credibility. With regard to political economy, most consolidation episodes were implemented shortly after an election. More than half of the governments that had started consolidation were re-elected, and some even strengthened consolidation efforts after then. In some cases, an incoming government of a different political colour pursued consolidation
Keywords: Economics